The clinical impact of conventional therapies for adults and adolescents suffering from eosinophilic esophagitis, a type 2 inflammatory chronic disease, and their economic consequences in Italy: Systematic literature review and meta-analysis - Giorgio Walter Canonica, MD; Gherardo Mazziotti, MD, PhD; Alessandro Repici, MD; Massimiliano Povero, PhD; Luca Castello, MSc; Lorenzo Pradelli, MD; Miryana Dobreva, MSc; Francesca Fanelli, MSc; Jean Pierre Saab, MD; Edoardo Vincenzo Savarino, MD, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Eosinophilic esophagitis (EoE) is a chronic inflammatory disorder marked by eosinophilic infiltration of the esophageal mucosa. Despite advances in understanding and management, optimal therapeutic strategies remain unclear, with conflicting guidelines. Objective: We sought to evaluate effectiveness and safety of topical corticosteroids (TCSs) and proton pump inhibitors (PPIs) in managing EoE and their economic implications in Italy. Methods: MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials were searched up to December 2023 and 78 publications were included, covering treatment outcomes and adverse events. Meta-analyses were performed to evaluate treatment efficacy and safety across various patient populations and study designs. Results: TCSs showed superior efficacy over PPIs in achieving histologic, endoscopic, and partial clinical responses. Older patients responded better to both treatments. Treatment outcomes varied by sex and presence of atopic conditions. TCSs discontinuation increased the risk of clinical relapse (0.70 cases per person-year), whereas continuous use was linked to a rise in nonserious adverse events (dilation, infections, upper respiratory tract infections, and skin disorders). Economic analysis indicated cost variations based on treatment regimens and follow-up protocols, with dilation and relapse being significant cost drivers in Italy. Conclusions: This review provides insights into efficacy, safety, and economic impact of TCSs and PPIs in managing EoE. TCSs were more effective in achieving histologic and endoscopic responses, whereas PPIs were effective in reducing symptoms. Standardized treatment guidelines are needed because of varied treatment efficacy across studies. Future research and new therapies may enhance outcomes and reduce health care costs, improving patient quality of life.